Impactos financieros sobre los efectos generados en el sector cooperativo nivel III en el departamento de Boyacá en tiempos de pandemia - Carlos Gutierrez, Humberto (Universidad Antonio Nariño, 2022)
This degree work analyzes the financial effects that occurred in the level III cooperative sector in the department of Boyacá, for the application of descriptive methodology using field research resources, characterization surveys; The financial structure situation and the new behaviors for the sector in question are analyzed, in the different components that give rise to the financial statements, achieving as a result the determination of the effects that occurred in the achievement of surpluses and the administration of the capital of job